Case report: Successful treatment of a rare case of combined parathyroid adenoma, cervical bronchogenic cyst, and tracheal diverticulum with gasless endoscopic resection of neck masses via an axillary approach: A case report and literature review - Lu, Dong-Ning; Zhang, Wan-Chen; Zheng, Chuan-Ming; Ge, Ming-Hua; Xu, Jia-Jie (Frontiers in Oncology, 2022)
Parathyroid adenoma (PA), one of the most common causes of hyperparathyroidism, generally involves a single parathyroid gland and is manifested as hyperparathyroidism. Bronchogenic cysts are rare congenital cystic lesions caused by a development malformation in bronchi during the embryonic period, which mostly occur in the lung and mediastinum, with an extremely low morbidity rate in the neck. A 27-year-old young female was found to suffer from hyperparathyroidism on routine physical examination, and further examination suggested a cystic lesion in the right inferior parathyroid area combined with a tracheal diverticulum. Therefore, she was initially diagnosed with cystic hyperplasia of the parathyroid glands complicated by a tracheal diverticulum. Gasless endoscopic resection of neck masses via an axillary approach was performed because of the high requirements for the surgical cosmetic effect of the patient. During the surgery, we observed that the preoperatively diagnosed cystic lesion was a combination of two masses, which were successfully resected under endoscopy. Based on the postoperative pathology and clinical features, the patient was eventually diagnosed with a rare case of triple diseases including PA, cervical bronchial cyst, and tracheal diverticulum. Now, the patient recovered well as per the follow-up with no signs of recurrence and was extremely satisfied with the cosmetic effect of the surgery.